Turkish folk medicinal plants, part V: Babaeski (Kirklareli) - (:unkn) unknown (My University, 2007)
In this study, 62 folk medicinal plants from Babaeski (Kιrklareli) are presented. Among them 46 species are wild and 16 species are cultivated plants. The folk medicinal plants are mostly used for the treatment of kidney, stomach and prostate ailments, rheumatism, cold, hemorrhoids, diabetes, asthma and bronchitis.
Keywords: Babaeski; Folk medicine; Kirklareli; Medicinal plants; Turkey